Note on Octavius 5.12 of Minucius Felix: An Unexpected Senecan Allusion - Valencia Constantino, Genaro (Revista Archai, 2024)
In this note an allusion recreated from Seneca’s De providentia is rescued as it was hidden in the Octavius of Minucius Felix, who recovers and adapts some topics from the Senecan text in a few brief lines which have been hitherto practically unnoticed; if the allusion is verified, a more recent reading of Seneca’s writing would make full argumentative sense.